UKRAINIAN HISTORICAL THOUGHT AT THE PRESENT STAGE (ABOUT A. PALIA'S BOOK «A SHORT COURSE IN THE HISTORY OF UKRAINE») - Dubrovskii A.M. (Вестник Брянского государственного университета)
The article discusses the content of A. Palia's book "A Short course in the History of Ukraine". Paliy is the author of a number of books about Ukraine. His "Short Course" is addressed to a wide range of readers. In 2018, the third edition of this work was published. A. Palia's book consists of 80 essays. There are no new facts, new ideas in the book. In the essays, certain topics are covered in great detail, others are wrongfully given much less attention by the author. Covering the history of Ukraine, A. Paliy does not use falsification. He prefers the method of silence, in which the reader learns a partial truth that is convenient for the author. Incomplete but reliable information looks convincing to the reader, but he cannot find out the true story. An important feature of A. Palia as a researcher is the desire to put forward the great ancestors of the Ukrainian people, simplistically linking the origin and achievements of this people with various other ancient peoples. The book often compares Ukraine with Russia, and Russia is always represented as a backward country, its people are less talented than Ukrainians. Humiliating Russia, the author glorifies Ukraine. Russia is shown in the book as a country that is constantly hostile to Ukraine.